2004
DOI: 10.1002/job.257
|View full text |Cite
|
Sign up to set email alerts
|

A field study of group diversity, workgroup context, and performance

Abstract: SummaryWe explore how the context of an organizational workgroup affects the relationship between group diversity and various performance outcomes. In particular, we theorize and empirically examine the moderating effects of three categories of workgroup context variables: cultures (people-and competition-oriented), strategies (stability-, growth-and customer-oriented), and human resource practices (diversity-and training-oriented). We perform analyses on 1528 workgroups from a Fortune 500 information-processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
214
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(237 citation statements)
references
References 92 publications
7
214
0
10
Order By: Relevance
“…Although diversity may increase productivity under certain conditions (see above), research shows it may also negatively affect team performance (Jehn and Bezrukova 2004;Thomas 1999). For instance, the abovementioned threats show that a diverse team may be more difficult to manage; diversity may reduce social cohesion and increase the risk of miscommunication and conflict.…”
Section: Threats Associated With Cultural Diversitymentioning
confidence: 99%
“…Although diversity may increase productivity under certain conditions (see above), research shows it may also negatively affect team performance (Jehn and Bezrukova 2004;Thomas 1999). For instance, the abovementioned threats show that a diverse team may be more difficult to manage; diversity may reduce social cohesion and increase the risk of miscommunication and conflict.…”
Section: Threats Associated With Cultural Diversitymentioning
confidence: 99%
“…On the other hand, another study found that a collectivist culture had few and mixed significant effects on the relationship between diversity and performance (Jehn & Bezrukova, 2004). Therefore, the impact of these norms is unclear.…”
Section: Collectivist Team Norms and Superordinate Team Identitiesmentioning
confidence: 99%
“…Recent research on team norms hypothesizes that outcomes in diverse teams are strengthened by cooperative, collectivist norms and cultures (Chatman & Flynn, 2001;Chatman et al, 1998;Chatman & Spataro, 2005;Jehn & Bezrukova, 2004). Researchers argue that cooperative norms improve team outcomes by heightening the salience of superordinate team identities and interests and downplaying those of individuals (Chatman & Flynn, 2001;Chatman et al, 1998).…”
Section: Collectivist Team Norms and Superordinate Team Identitiesmentioning
confidence: 99%
“…We underline that, in principle, diversity refers to a number of different dimensions -from task skills to relational skills, and from political preferences to sexual liking (van Knippenberg, De Dreu and Homan, 2004). In any case, diversity is dependent on the context and situation and thus, group and organizational factors have to be considered (Jehn and Bezrukova, 2004). Cultural diversity comprises different backgrounds of members of work groups and teams related to national cultures (Barinaga, 2007).…”
Section: Challenges For College Students and Graduatesmentioning
confidence: 99%